2016
DOI: 10.7566/jpsj.85.044707
|View full text |Cite
|
Sign up to set email alerts
|

Of Substitution and Doping: Spatial and Electronic Structure in Fe Pnictides

Abstract: A highly intriguing aspect in iron-pnictide superconductors is the composition-dependent electronic structure, in particular the question if and how charge carriers are introduced to the system upon substitution of Ba by alkali metals or of Fe by other transition metals, TM. We report on a systematic study of spatial structure and electronic states by x-ray diffraction and x-ray absorption on a large number of compositions in the (Ba,K)(Fe,TM) 2 As 2 family. The coherent combination of detailed structural info… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…A systematic study of the electronic structures of the doped BaFe 2 As 2 and SrFe 2 As 2 has been reported by XAS at L 2,3 absorption edge. 27,28 Although the shift in the energy position of the L 3 -edge observed maximum peak, the study indicated that the doping plays a lesser role for pnictide superconductivity and magnetism. We note that the XAS study at the Fe and As K absorption edges was advantageous because we now know the spin state and the d-p hybridization, respectively.…”
Section: Introductionmentioning
confidence: 84%
“…A systematic study of the electronic structures of the doped BaFe 2 As 2 and SrFe 2 As 2 has been reported by XAS at L 2,3 absorption edge. 27,28 Although the shift in the energy position of the L 3 -edge observed maximum peak, the study indicated that the doping plays a lesser role for pnictide superconductivity and magnetism. We note that the XAS study at the Fe and As K absorption edges was advantageous because we now know the spin state and the d-p hybridization, respectively.…”
Section: Introductionmentioning
confidence: 84%
“…Borides with networks of boron atoms: crystal structure of AlB 2 (ICSD 193381, AlB 2(hex) structure). [295] Boron atoms are in gray, metal atoms are in blue.…”
Section: Superconductivitymentioning
confidence: 99%
“…The variety of suitable tuning parameters includes diverse chemical substitutions [17,20], hydrostatic pressure [17,21,22], epitaxial strain in thin films [23][24][25] and uniaxial pressure [26][27][28][29][30]. In Ca(Fe 1−x Co x ) 2 As 2 , substitution of Co for Fe suppresses a coupled first-order magneto-structural transition at T s,N and induces superconductivity with a maximum T c of 16 K [31].…”
mentioning
confidence: 99%